L2 willingness to communicate (WTC) and international posture in the Polish educational context - Mystkowska-Wiertelak, Anna; Pietrzykowska, Agnieszka (Studies in Second Language Learning and Teaching, 2011)
Speaking, the language skill whose mastering appears to be the ultimate aim of every attempt at learning a foreign language, constitutes a formidable challenge. Apart from involving the online interaction of complex processes of conceptualization, formulation, articulation and monitoring (Levelt, 1989), it appears prone to numerous psychological and social influences that, being difficult to control, may consistently hinder development. One of such factors, closely related to the concept of anxiety, is L2 willingness to communicate (WTC), called “the most immediate determinant of L2 use” (Clement, Baker, & MacIntyre, 2003, p. 191). Perceived as either a personality trait or/and a context-related feature, WTC seems capable of accounting for a person’s first and second language communication. Interestingly it can be related to the learner’s disposition towards the target language culture, general interest in international affairs, willingness to travel and sustain contacts with speakers of other languages, which, defined as international posture (Yashima, 2002), serves as a strong predictor of success in language learning. The present paper reports the results of a survey conducted among 111 students of English, in the majority prospect teachers of English. The aim was to establish the degree of correlation between their international posture and WTC. The results do not corroborate the outcomes of other studies performed in the field (cf. Yashima, 2002, 2009), which might point to the unique characteristics of the Polish educational context.